A report on the practice-in-industry training in fish preservation - Garcia, Brenda P. (College of Fisheries, University of the Philippines, 1967)
A good many Filipinos are dependent on fish either for their livelihood or for their main viand; therefore, our fishery industries are essential to our socio-economic status. Although this is a known accepted fact, our fishery industries have received only half-hearted support. Consequently, we are far from being self-sufficient in this area as evidenced by the fact that the Philippines imported P61, 692,012 worth of fish and fish products for the year 1965. Fisheries statistics of the Philippines, an official publication of the Philippine Fisheries Commission, reveals that the Philippines importations of fish and fish products beginning 1961 have been increasing. The admittedly slow progress of our fishery industries is due to the glaring lack of trained manpower qualified to raise and sustain our production and consumption of fish and fish products. The need for highly trained men in fisheries technology in the different fishery industries, in the governments fisheries service and in the fisheries teaching profession had been recognized with the conversion of the former Philippine Institute of Fisheries Technology (PIFT) into the College of Fisheries of the University of the Philippines when the Bureau of Fisheries was recognized on January 16, 1957. The Fishery courses, however, does not yet attract students like the other popular courses such as commerce, engineering, medicine, and etc. our people, as a whole. Have still to be shown that the fishery courses are just as lucrative, dignified, and honorable as the other courses. Fishery graduates have important roles in hastening the development of our fishery industries and giving the Philippines her rightful place among the fishing countries of the world. The two and one-half year course leading to a certificate in fisheries is essentially vocational in character. It is intended to enable the graduates to acquire a reasonable degree of technical skill necessary to succeed in fisheries and allied ventures, or in securing employment in fisheries firms. In line with this aim, graduating students have been required the practice-in-industry training which may be undertaken under conditions wherein the equipment and facilities are similar or comparable to those on the fishery industry, either on the home industry level or on the commercial scale. This practice-in-industry training further develops the student's ability through actual and research work.